Investıgatıng Taxpayers Intentıon To Accept Onlıne Tax Fıllıng System: An Indonesıan Perspectıve - Umi Nandiroh; Heri Pratikto; Ludi Wishnu Wardana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The internet of things has encouraged the directorate general of taxes to reform the tax administration system, and the goal is none other than to provide optimal services to taxpayers. One form of reform carried out is e-filling media for making and reporting tax returns. This study examines the factors that influence taxpayers' interest in using e-filling with the UTAUT model. The quantitative approach was employed as the primary research design in this study. Purposive sampling was used as a sampling methodology, with the structured questionnaire's five-point Likert scale serving as an assessment scale and data collection tool. The bootstrap approach was used to examine the hypotheses given. The results show that performance expectations and facilitating conditions positively affect behaviour intention to accept e-filling. Effort expectations and social influences do not affect behaviour intention to accept e-filling.